The Concept Of Bale Kambang In The Architecture Of Kanoman Palace Cirebon - Nia Yunia Lestari; Shirli Putri Asri; Rachmat Kurnia (International journal of technology and education research, 2024)
Bale kambang is one of the traditional architectural spatial concepts that is always present at the core of a palace or kraton. The concept of bale kambang is generally known as a water garden and is closely related to the influence of Hindu-Buddhist culture that developed in the Archipelago from the 4th to the 15th century. This research aims to examine the philosophical concept and the concept of Bale Kambang in the architecture of the Kanoman Palace, which is influenced by the remnants of Hindu-Buddhist, Chinese, and Islamic cultures. There are four processes of study in this research: first, a review of the philosophy of the water element in Hindu, Buddhist, and Islamic beliefs; second, a review of the architecture of water gardens and floating pavilions based on their history and development; third, a comparative review of several spatial patterns of floating pavilions in Javanese and Balinese palaces; fourth, an interpretation of the symbols and meanings of floating pavilions.The methodology used is a qualitative approach with a descriptive-analytical method, including literature study, field research, and interviews with experts in Cirebon history and culture. The research results show that the concept of Bale Kambang in the architecture of the Kanoman Palace is represented through two types of palace buildings, namely Witana and Bangsal Jinem. Each of these buildings has the symbol of Meru and a small pond adorned with coral stones as symbols of the sacred water element. Based on its history and development, the Bale Kambang of the Kanoman palace in Witana has a shape similar to the Bale Kambang of the Kasepuhan palace, while in the Bangsal Jinem, the Bale Kambang is represented on the sultan's throne as a place to receive honored guests. Based on symbols and meanings, the concept of the floating pavilion in the Kanoman palace reflects purity, harmony between humans and nature, and spirituality that connects the material and transcendental worlds. This symbolism enriches the identity that the floating pavilion is not always in the form of a building on a pond, but can be reflected by sacred objects considered as Mount Meru and the presence of water elements as a sacred medium, which altogether express the spiritual and cultural values in the Kanoman palace. This research is expected to contribute to enhancing understanding of the symbolism of the bale kambang concept, which reflects the historical and cultural dynamics of the Kanoman palace.